An analogue front-end ASIC prototype designed for PMT signal readout - 刘建峰 赵雷 于莉 梁宇 秦家军 杨云帆 邬维浩 刘树彬 安琪 (Chinese physics C, 2016)
The Water Cherenkov Detector Array （WCDA） is one of the core detectors in the Large High Altitude Air Shower Observatory （LHAASO）, and it consists of 3600 photomultiplier tubes （PMTs）. Both high resolution time and charge measurement are required over a large dynamic range from 1 photoelectron （P.E.） to 4000 P.E. The prototype of an analogue front-end Application Specific Integrated Circuit （ASIC） fabricated using Global Foundry 0.35 μm CMOS technology is designed to read out the PMT signal in the WCDA. This ASIC employs leading edge discrimination and an （RC）4 shaping structure. Combined with the following Time-to-Digital Converter （TDC） and Analog-to-Digital Converter （ADC）, both the arrival time and charge of the PMT signal can be measured. Initial test results indicate that time resolution is better than 350 ps and charge resolution is better than 10% at 1 P.E. and better than 1% with large input signals （300 P.E. to 4000 P.E.）. Besides, this ASIC has a good channel-to-channel isolation of more than 84 dB and the temperature dependency of charge measurement is less than 5% in the range 0 50℃.